The Elderly Educators in Their Quest for Lifelong Learning: Some Stories to Tell - Blancia, Maylin Marabe; Fabros, Minerva T; Blancia, Norman o (International Journal of Management Excellence (ISSN: 2292-1648), 2018)
This phenomenological study explored the lived experiences of 20 elderly teachers, 50 to 65 years old, still in the service and enrolled in post graduate education. Through in-depth interviews of 10 informants and focused group discussion of 10 participants, the data were gathered and subjected to thematic analysis. The results revealed that the elderly teachers decided to enroll in post graduate education for reasons of dealing with age-specific issues and expectations, balancing personal and professional responsibilities, being infused with young brood and new perspectives, aspiring for career advancement opportunities, enhancing professional portfolio, and rearranging needs and priorities were the themes. The themes for the challenges of the elderly educators connected to their quest for lifelong learning included, balancing and prioritizing, keeping abreast with technology and new sources of knowledge, being optimistic and positive, and being determined and resolute. The insights of lifelong learning shared by informants and participants were, professional advancement brings promotion opportunities, lifelong learning is personal development, age does not matter in learning, and lifelong learning has its rewards. What is notable in this study is the participants’ being still active and generative, their resiliency to face the challenges, and their insights of wisdom, hope, and faith.